Transition, hedge, or resist? Understanding political and economic behavior toward decarbonization in the oil and gas industry. Issue 6 (21st November 2022) - Green, Jessica; Hadden, Jennifer; Hale, Thomas; Mahdavi, Paasha
Abstract: Many oil and gas firms claim they are going green. But are they actually walking the talk? We analyze the political and economic behavior of publicly traded oil majors to understand the degree to which they are decarbonizing. We collect a wide range of firm-level data from 2004 to 2019, including a novel measurement of political behavior based on original coding of corporate earnings calls. Our analysis yields four main findings. First, firms' political and economic behavior are not necessarily correlated, demonstrating the value of a two-pronged political economy approach to the study of multinational firms. Second, not a single firm is shifting away from fossil fuels during the time frame studied. Changes in business behavior have been relatively modest in scope. The most ambitious firms are engaging in hedging—mitigating risk through diversification rather than moving toward decarbonization. Third, major oil and gas firms meliorate anti-climate political positions between 2010 and 2018. Finally, firms with greater progress towards decarbonization tend to be located in or sell their products in jurisdictions with more stringent environmental regulation, have smaller refining sectors, and be involved in more industry coalitions.